ANALYSIS OF TECHNOLOGY ACCEPTANCE MODEL USERS OF FLIGHT TICKET RESERVATIONS SERVICES OF PT LION MENTARI AIRLINE - Khasanah Khasanah; Sabda Budi Sudarsono; Albaar Rubhasy; Yefri MC Liu; Rini Sulistyowati (Jurnal TAM (Technology Acceptance Model), 2019)
PT Lion Mentari Airline seeks to create innovations that pay more attention to the intensity and ease for their service users ie the airline ticket reservation system online or commonly known e-ticketing is a way of documenting the process of selling airline tickets from the user's travel activities without issuing physical evidence. This study aims to: (1) Perceived ease of use correlates to the perceived usefulness of the Airline Reservations Reservations Service at PT Lion Mentari Airlines online. (2) Perception of the perceived usefulness of the system has a positive effect on the attitude toward the use of the system (attitude toward using) Flight Booking Service at PT Lion Mentari Airlines Online (3) Perceived ease of use has a positive effect on attitude toward the use of the system (attitude toward using) Airline Booking Service at PT Lion Mentari Airlines Online (4) Attitude toward the use of the system (attitude toward using) positively influence the behavioral tendency to keep using the system (behavioral intention to use) Services Airline Ticket Reservation At PT Lion Mentari Airlines Online. This research uses four modified variables from previous Technology Acceptance Model (TAM) research model, namely: perceived usefulness perception as first independent variable (X1), perception ease of information system (perceived e asy of use) as the second independent variable (X2),), the perception of attitude toward the use of information system (attitude toward using) as the third independent variable (X3) and behavioral interest of the use of information system (Behavior Intention To Use) as dependent variable (Y).